Turkish folk medicinal plants, part III: Sile (Istanbul) - (:unkn) unknown (My University, 2000)
In this paper, forty-three folk medicinal plants from Sile (Turkey) have been reported. Among them 35 species were wild and eight species were cultivated plants. The folk medicinal plants have been mostly used for the treatment of eczema, stomach and kidney ailments, asthma, cough, diabetes, and wounds.
Keywords: Humans; Turkey; Plants, Medicinal; Medicine, Traditional